2012
DOI: 10.1097/brs.0b013e3182474d8b
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Trauma in Mainland China From 2001 to 2007

Abstract: This is the first large-scale epidemiological study of spinal injury in Mainland China. The results obtained have important implications for future public health care planning, public safety, and resource allocation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(39 citation statements)
references
References 16 publications
(9 reference statements)
1
32
1
2
Order By: Relevance
“…[13][14][15][16][17] For the spinal manifestations, it has been further shown that in end-stage DISH subjects, due to the inability of the stiff spine to absorb tearing forces, the vertebral column becomes more vulnerable to trauma which leads to fractures even after relatively low-energy trauma. [18][19][20] Therefore, the group unequivocally confirmed that due to the pathologically increased new bone formation, particular attention needs to be drown to the research of the disease-related biomechanical changes. In addition, involvement of the cervical spine and proliferative bone changes in its anterior part can lead to mechanical airway obstruction, difficulties with swelling and may also complicate medical procedures that require access to the upper airways and the digestive systems.…”
Section: Clinical Manifestationsmentioning
confidence: 95%
“…[13][14][15][16][17] For the spinal manifestations, it has been further shown that in end-stage DISH subjects, due to the inability of the stiff spine to absorb tearing forces, the vertebral column becomes more vulnerable to trauma which leads to fractures even after relatively low-energy trauma. [18][19][20] Therefore, the group unequivocally confirmed that due to the pathologically increased new bone formation, particular attention needs to be drown to the research of the disease-related biomechanical changes. In addition, involvement of the cervical spine and proliferative bone changes in its anterior part can lead to mechanical airway obstruction, difficulties with swelling and may also complicate medical procedures that require access to the upper airways and the digestive systems.…”
Section: Clinical Manifestationsmentioning
confidence: 95%
“…In the study by Liu et al 10 and Erdogan et al 11 investigating traumatic vertebral fractures, patients were mostly aged between 30-50 years (47 and 52%, respectively), whereas in our study patients were mostly (46%) aged between 40-60 years and approximately a quarter of the patients were over 65 years of age. Osteoporotic vertebral fractures may occur without trauma; nonetheless, our results suggest traumatic vertebral fractures are also remarkably frequent in elderly population.…”
Section: Discussionmentioning
confidence: 55%
“…Osteoporotic vertebral fractures may occur without trauma; nonetheless, our results suggest traumatic vertebral fractures are also remarkably frequent in elderly population. Previous studies have reported that vertebral fractures were observed 1.9-3.3-fold more frequent in men than in women 2,4,10,12,13 . Contrary to these results, we found male-to-female ratio as 1.5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 As such, developing nations are expected to have marked increases in SCI prevalence in the near future. 2 Although SCI is widely considered a condition primarily associated with a loss of motor ability, SCI also results in other important limitations such as severe cardiovascular dysfunction. 3 After SCI, supraspinal regulation of autonomic function is disrupted.…”
Section: Introductionmentioning
confidence: 99%